Fabrication of a Flexible Amperometric Glucose Sensor Using Additive Processes. (1st January 2015) - Du, Xiaosong; Durgan, Christopher J.; Matthews, David J.; Motley, Joshua R.; Tan, Xuebin; Pholsena, Kovit; Árnadóttir, Líney; Castle, Jessica R.; Jacobs, Peter G.; Cargill, Robert S.; Ward, W. Kenneth; Conley, John F.; et al.
Abstract : This study details the use of printing and other additive processes to fabricate a novel amperometric glucose sensor. The sensor was fabricated using a Au coated 12.7 μm thick polyimide substrate as a starting material, where micro-contact printing, electrochemical plating, chloridization, electrohydrodynamic jet (e-jet) printing, and spin coating were used to pattern, deposit, chloridize, print, and coat functional materials, respectively. We have found that e-jet printing was effective for the deposition and patterning of glucose oxidase inks with lateral feature sizes between ∼5 to 1000 μm in width, and that the glucose oxidase was still active after printing. The thickness of the permselective layer was optimized to obtain a linear response for glucose concentrations up to 32 mM and no response to acetaminophen, a common interfering compound, was observed. The use of such thin polyimide substrates allow wrapping of the sensors around catheters with high radius of curvature ∼250 μm, where additive and microfabrication methods may allow significant cost reductions.